A SISTEMATIZAÇÃO DA ASSISTÊNCIA DE ENFERMAGEM (SAE) APLICADA NA SAÚDE DA CRIANÇA: UM ESTUDO DE CASO - Dallabrida, Francieli A.; Lauter, Dagmar S.; Ribeiro, Carla P.; Barasuol, Mônica E. C.; Pettenon, Marinez K. (Salão do Conhecimento, 2013)
Resumo